"Savor the earth to save it!"—The pedagogy of sustainable pleasure and relational ecology in a place-based public culinary culture. Issue 1 (2nd January 2017) - VanWinkle, Tony N.
ABSTRACT: Sustainability has become a keyword in popular discourses in the age of the celebrity chef. As such, chefs and other actors working in the visible spaces and venues of a shared US public culinary culture have become powerful spokespersons for sustainable food production, consumption, and localization. Unlike catastrophist discourses of environmentalisms' of the past, however, this new discourse is often framed in terms of a politics of pleasure that redefines deliberate and considered hedonism as a kind of transformative eco-culinary engagement. In self-assigned missionary roles, chefs and other prepared food producers are often engaging in a very deliberate pedagogical project that link sensuality and sustainability. Likewise, and equally important to these efforts, is the centrality of regard—that is, attempts among chefs to re-embed exchange relations between producers and consumers, often serving as the critical interlocutors in such reassertions. This article is an exploration of how such processes have played out in the public culinary context of Knoxville, Tennessee and vicinity. As a mid-size city in the heart of southern Appalachia's Ridge and Valley sub-region, Knoxville is undergoing a familiar process of urban revitalization that includes a robust food service sector. Amid shifting demographics and media flows bringing more cosmopolitan influences to the region, a range of actors have grounded these in a regionally specific food and farming heritage in order to reconnect consumers and producers and cultivate a more sustainable and mutualistic local food system.